Mätning av stammens tvärsnittsarea med hjälp av klave jämfört med diametermåttband i det praktiska skogsbruket - Eneman, Björn; Olsson, Christoffer (SLU/School for Forest Management, 2019)
The two most common ways of measuring the breast height diameter of a tree stem is to use a caliper or a diameter measuring tape. In Sweden there is a tradition of using a caliper when estimating the volume of a forest. From an international perspective the diameter measuring tape is the more common tool.